BMI1, ALDH1A1, and CD133 Transcripts Connect Epithelial-Mesenchymal Transition to Cancer Stem Cells in Lung Carcinoma - Ana Koren; Matija Rijavec; Izidor Kern; Eva Sodja; Peter Korosec; Tanja Cufer (Stem Cells International)
Epithelial-mesenchymal transition (EMT) is the underlying mechanism of tumor invasion and metastasis. Evidences from lung cancer cellular models show EMT can trigger conversion to a cancer stem cell (CSC) phenotype. In this study, we assessed mRNA expression levels of EMT-inducing transcription factors (BMI1, TWIST1), CSC (CD133, ALDH1A1), and epithelial (EpCAM) markers in primary tumor and whole blood samples obtained from 57 patients with operable non-small-cell lung cancer (NSCLC) as well as in circulating tumor cells (CTCs) of 13 patients with metastatic disease; then possible associations between marker expressions were evaluated. In primary tumors as well as in whole blood, correlations between BMI1 and ALDH1A1 and between BMI1 and CD133 mRNA expressions were identified. No correlations between TWIST1 and CSC markers were observed. BMI1 mRNA expression in tumors positively correlated with BMI1 mRNA expression in blood. The immunohistochemical analysis confirmed coexpression of BMI1 and CSC markers in tumors. Gene expression profiling in CTCs revealed upregulated expression of EMT/CSC markers in CTCs. Our results suggest CSCs are present in both, tumor tissue and blood of NSCLC patients, whereas Bmi1 may play an important role in initiation and maintenance of CSCs and might be involved in the blood-borne dissemination of NSCLC.